Eliminate harmful side – effects of Controls System by designing Activity – Based Responsibility Accounting model - جاسم, نصيف; فرج, مشتاق كامل; ابراهيم, سحر طلال (Journal of Economics and Administrative Sciences, 2011)
This research has come out with that, function-based responsibility accounting system has harmful side – effects preventing it of achieving its controlling objective, that is, goal congruence, which are due to its un integrated measures, its focus on measuring measurable behaviors while neglecting behaviors that are hardly measured, and its dependence on standard operating procedures.In addition, the system hypotheses and measures are designed to fit previous business environment, not the current environment. The research has also concluded that the suggestive model, that is, activity-based responsibility accounting is designed to get ride of harmful side – effects of function-based responsibility system by eliminating the reasons behind these previous effects ,moreover, model hypotheses, objectives and measures fit current business environment and its requirements.